THE EFFECT OF USING QUESTION AND ANSWER RELATION-SHIP (QAR) STRATEGY ON READING COMPREHENSION - Abdul Rahman Siagian (Linguistik : Jurnal Bahasa dan Sastra, 2020)
Problem in this research is how to improve reading comprehension by using Question and Answer Relationship (QAR) strategy at the X Grade of SMA Negeri 1 Batangtoru. Thus, the objective of this research is to know if there is any significant effect of using Question and Answer Relationship (QAR) strategy to students’ reading comprehension at the X grade of SMA Negeri 1 Batangtoru. Experimental research method is the research method that is used by the researcher to conduct this research. Population  of this research was the X students of SMA Negeri 1 Batangtoru, namely 151 students while for tecnique of taking the sampling by using cluster sampling that is 36. The instrument of this research is test about reading comprehension.Based on the data that has been analyzed, it can be found that (1) the students’ achievement in reading comprehension by  using Question and Answer Relationship (QAR) strategy) at the X grade of SMA Negeri 1 Batangtoru is “enough” (69.72), (2) their value before  using Question and Answer Relationship (QAR) strategy at the X grade of SMA Negeri 1 Batangtoru can be categorized “enough” (61.94), and (3) there was a significant effect of using Question and Answer Relationship (QAR) strategy on reading comprehension at the X Grade of SMA Negeri 1 Batangtoru. It meant that the hypothesis was accepted.